ادارة الازمات كمدخل للتغيير المؤسساتي مع دراسة حالة بالمستشفي الجهوي كعرار السبتي _ سوق أهراس - مالك بوشوك; عماد سوالمية (My University, 2021)
This study aimed to test the existence of a relationship between crisis management and institutional change, as the study relied on a questionnaire consisting of 42 phrases, which was relied on the SPSS program, and the questionnaire was distributed to several employees of the regional hospital as KArar Al-Sabti - Souk Ahras _. The study concluded that there is an impact relationship of crisis management on institutional change in hospital institutions ........................................... هدفت هذه الدراسة الى اختبار وجود علاقة بين ادارة الازمات والتغيير المؤسساتي ، حيث اعتمدت الدراسة على استبانة مكونة من 24 وتم توزيع الاستبانة على عدة من موظفي المستشفى الجهوي كعرار السبتي _سوق أهراس SPSS عبارة ، حيث تم الاعتماد على برنامج وقد خلصت الدراسة الى وجود علاقة تأثير لادارة الازمات على التغيير المؤسساتي في المؤسسات الاستشفائية